PENGEMBANGAN USAHA KOPI BERBASIS KESWADAYAAN MASYARAKAT DI DESA GENTING KECAMATAN JAMBU KABUPATEN SEMARANG TAHUN 2024 - Ratih Rahayu (Marsialapari: Jurnal Pengabdian Kepada Masyarakat, 2024)
This research aims to analyze strategies for developing coffee businesses based on community self-reliance and the role of self-reliance in supporting the sustainability of coffee businesses in Genting Village, Jambu District, Semarang Regency. The research uses a qualitative descriptive approach with data collection methods through interviews, observation and documentation. Data analysis techniques are carried out by data reduction, data presentation, and drawing conclusions. The validity of the data was tested using triangulation of sources, techniques and time.   The research results show that the coffee business development strategy involves easy access to capital, development of business infrastructure, community economic empowerment, development of business networks, as well as increasing human resource capacity and access to technology. Community self-sufficiency makes a positive contribution to economic, social and environmental aspects, by creating prosperity and sustainability for future generations. These findings show the importance of self-reliance-based collaboration in increasing the competitiveness and sustainability of local businesses.